2014
DOI: 10.1371/journal.pone.0113433
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Escherichia coli and Salmonella Strains Isolated from Stray Dog and Coyote Feces in a Major Leafy Greens Production Region at the United States-Mexico Border

Abstract: In 2010, Romaine lettuce grown in southern Arizona was implicated in a multi-state outbreak of Escherichia coli O145:H28 infections. This was the first known Shiga toxin-producing E. coli (STEC) outbreak traced to the southwest desert leafy green vegetable production region along the United States-Mexico border. Limited information exists on sources of STEC and other enteric zoonotic pathogens in domestic and wild animals in this region. According to local vegetable growers, unleashed or stray domestic dogs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 49 publications
(71 reference statements)
11
27
0
1
Order By: Relevance
“…This is consistent with several surveys in dogs (32, 39, 45, 73). Other studies (42, 46, 58, 7477) have reported younger and older animals as having a greater likelihood of serious infection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with several surveys in dogs (32, 39, 45, 73). Other studies (42, 46, 58, 7477) have reported younger and older animals as having a greater likelihood of serious infection.…”
Section: Discussionsupporting
confidence: 93%
“…This is similar to the findings of many other surveys (32, 44, 45, 84, 85, 8991). Two of the isolates in the present study were resistant to three or more antibiotics.…”
Section: Discussionsupporting
confidence: 92%
“…They represented that 54.54% of E. coli isolates were STEC. In addition to our results and also finding of Momtaz et al, 13 Hemmatinezhad et al 14 and Ranjbar et al, 15 simultaneous presences of stx1, stx2, eaeA and ehly virulence factors have also been reported by Franz et al, 17 JayRussell et al 18 and Kabiru et al 19 …”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) have examined the ecology of foodborne pathogens in agricultural environments, and several (22)(23)(24)(25)(26)(27) have used GIS and geospatial analysis. For example, Chapin et al (26) used GIS to organize and extract remotely sensed data to show that different species of Listeria occupy distinct ecological niches in agricultural and natural environments.…”
mentioning
confidence: 99%